Indexing large geographic datasets with compact qualitative representation. Issue 6 (2nd June 2016) - Long, Zhiguo; Duckham, Matt; Li, Sanjiang; Schockaert, Steven
ABSTRACT: This paper develops a new mechanism to efficiently compute and compactly store qualitative spatial relations between spatial objects, focusing on topological and directional relations for large datasets of region objects. The central idea is to use minimum bounding rectangles (MBRs) to approximately represent region objects with arbitrary shape and complexity and only store spatial relations that cannot be unambiguously inferred from the relations of corresponding MBRs. We demonstrate, both in theory and practice, that our approach requires considerably less construction time and storage space, and can answer queries more efficiently than the state-of-the-art methods.